1989
DOI: 10.1007/bf00453664
|View full text |Cite
|
Sign up to set email alerts
|

The effects of anesthesia of the tympanic membrane on eustachian tube function

Abstract: In our previous histological studies of the tympanic membrane, we reported the presence of encapsulated nerve corpuscles that are capable of detecting middle ear pressure. Based on these findings, the relation between sensory receptors in the tympanic membrane and tubal function was examined in a clinical study. Tubal function was tested during Valsalva maneuvers and its active equilibration. Function was recorded as a change of the static compliance of the tympanic membrane on an otoadmittance meter. To paral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
2

Year Published

1997
1997
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 6 publications
0
9
0
2
Order By: Relevance
“…The tympanic membrane, by virtue of the viscoelasticity of the lamina propria, has been theorized to act as a pressure regulator. Indirect evidence includes the finding of nerve endings in the drum, which act as “modified pacinian corpuscles.” 120,121 Further proof includes a dysfunction of the eustachian tube with iontophoretic anesthesia of the drum suggesting a possible neural connection between the tympanic membrane and tubal muscles 122 . It is also quite possible that the tensor tympani tendon also acts to modify the tone of the tensor palati muscle in response to movements of the pars tensa 123 …”
Section: Normal Tympanic Membranementioning
confidence: 99%
See 1 more Smart Citation
“…The tympanic membrane, by virtue of the viscoelasticity of the lamina propria, has been theorized to act as a pressure regulator. Indirect evidence includes the finding of nerve endings in the drum, which act as “modified pacinian corpuscles.” 120,121 Further proof includes a dysfunction of the eustachian tube with iontophoretic anesthesia of the drum suggesting a possible neural connection between the tympanic membrane and tubal muscles 122 . It is also quite possible that the tensor tympani tendon also acts to modify the tone of the tensor palati muscle in response to movements of the pars tensa 123 …”
Section: Normal Tympanic Membranementioning
confidence: 99%
“…"12°J21 Further proof includes a dysfunction of the eustachian tube with iontophoretic anesthesia of the drum suggesting a possible neural connection between the tympanic membrane and tuba1 muscles. 122 It is also quite possible that the tensor tympani tendon also acts to modify the tone of the tensor palati muscle in response to movements of the pars tensa.123…”
Section: Middle Ear Histology and Atmospherementioning
confidence: 99%
“…It is as yet unclear whether this reflex pathway is also capable of changing eustachian tube function, as measured above, but at least one report suggests that nociceptive nerves associated with the bulla can do this. Nagai et al [21] have shown that local anaesthesia of nerves in the tympanic membrane can adversely affect eustachian tube function in humans. Nagai et al [21] assumed that the anaesthetic was affecting encapsulated receptors they had previously identified in the tympanic membrane, but it may be that the anaesthetic was affecting unencapsulated CGRP-immunoreactive fibres, such as those we have described.…”
Section: Discussionmentioning
confidence: 99%
“…Tympanic plexus baroand chemoreceptors (35,36) trigger the moderately slow actuators. TM stress receptors (37,38) and Ruffini corpuscles in the PR fundus and posterior nasopharyngeal wall (39) trigger the fast actuators. Theoretically, acoustic clues gathered via the cochlea, proprioceptive receptors in the muscles, and sensors on other locations may be involved.…”
Section: Feedback Loop and The Concept Of Resonance Homeostasismentioning
confidence: 99%